Recycled plastic as bitumen modifier: The role of recycled linear low-density polyethylene in the modification of physical, chemical and rheological properties of bitumen. (1st September 2020) - Nizamuddin, Sabzoi; Jamal, Muhammad; Gravina, Rebecca; Giustozzi, Filippo
Abstract: The integration of various polymers in bitumen is common practice to reduce its thermal susceptibility. Nowadays, recycled materials are re-purposed in roads to improve the overall pavement performance and durability. Specifically, the use of soft plastics has been increasingly looked after by local governments and road authorities to possibly limit landfill, hence helping with the waste management issues experienced by many countries. This study evaluates the use of a very common and largely available soft plastic - recycled linear low-density polyethylene (R-LLDPE) - for modification of bitumen. To assess its applicability in the road sector, the base bitumen and R-LLDPE modified bitumen blends were compared through physical, chemical, rheological and thermal evaluation. It was observed that due the addition of high concentrations of R-LLDPE the viscosity and softening point were increased from 0.62 Pa s and 44.1 °C up to 5.75 Pa s and 122.3 °C, respectively, whereas the penetration value decreased from 59.3 to 14.3 (0.1 mm). A progressive increase in viscosity with increasing concentration of R-LLDPE indicates substantial reduction in workability due to the greater polymer-dominant phase. An increase in the intensities of peaks and the absence of new peaks during Fourier transform infra-red (FTIR) analysis confirms the successful blending of the recycled polymer into the bitumen matrix. The thermogravimetric analysis (TGA) shows that the modified bitumen had less evaporation and higher thermal stability than base bitumen. The rheological evaluation highlighted how the R-LLDPE addition significantly affected the thermo-susceptibility of the bitumen and improved the resistance to permanent deformation at high temperature and elastic recovery. Based on the overall findings of this study, it can be stated that R-LLDPE – if dosed correctly and sourced from homogeneous sources – can enhance the overall bitumen performance without significant drawbacks. In particular, 3% R-LLDPE is considered a suitable modification for most environmental conditions, whereas 6% R-LLDPE is only ideal for tropical climates. Higher dosage is not recommended. Graphical abstract: Image 1 Highlights: Soft plastics (L-LDPE) was recycled and blended with bitumen providing betterments. Up to 3% of recycled soft plastics was deemed suitable for bitumen modification. More than 6% recycled soft plastics greatly affected bitumen viscosity. Improved resistance to rutting (MSCR test) was identified with increased plastics. Controlled sources of waste plastics proved to be suitable to modify bitumen.